Waste Reduction Strategies: Factors Affecting Talent Wastage and the Efficacy of Talent Selection in Sport - Johnston, Kathryn; Baker, Joseph (Frontiers in Psychology, 2020)
Coaches are faced with the difficult task of identifying and selecting athletes to their team. Despite its widespread practice in sport, there is still much to learn about improving the identification and selection process. Evidence to date supports selection decisions (at different competitive levels) can be inaccurate, bias driven, and sometimes even illogical. These mistakes are believed to contribute to ‘talent wastage’, the effect of a coach’s wrongful selection and/or deselection of an athlete to/from a team. Errors of this scale can lead to negative repercussions for all stakeholders involved and therefore deserves further exploration. It is the purpose of this paper to shed light on the potential factors influencing talent wastage and to illuminate the possible psychological pitfalls when making decisions under uncertainty.